Microchannel plate lifetime experiment for the DIS and DES instruments on the Magnetospheric Multiscale Mission. (15th October 2018) - Mackler, D.; Avanov, L.; Barrie, A.; Chornay, D.; Gershman, D.; Giles, B.; Pollock, C.; Rager, A.; Smith, S.
Abstract: The stability of microchannel plate (MCP) gain with time impacts the success of long-term space plasma missions that use such detectors. Gain stability is of particular importance for the Fast Plasma Investigation (FPI) suite on NASA's Magnetospheric Multiscale (MMS) mission, which operates 64 independent MCP assemblies. Due to this massive number of sensors, there was not sufficient time to fully precondition all flight detectors prior to MMS launch. Therefore, an understanding of the change of MCP gain with time is vital to ensure quality FPI performance. We have conducted lifetime experiments with flight-grade FPI-like MCP assemblies for both ion and electron detectors. These experiments demonstrate that MCP gain stabilizes after ≈ 1.0 C/ c m 2 has been extracted from the plates. Based on these results, the FPI MCPs could potentially operate for 20+ years on-orbit. Highlights: Less than 1 C/cm 2 has been extracted from the FPI/DES MCPs on NASA's MMS mission. The rate of the required voltage changes for the DESs is significantly decreasing. Charge extracted from DIS is more than order of magnitude lower than DES. Based upon these MCP lifetime experiments, the FPI detectors could potentially provide high quality science data at least another 2-3 decades. Both DES and DIS flight spare MCPs exhibited stable detector efficiencies over lifetime testing.